2014
DOI: 10.1136/gutjnl-2014-307226
|View full text |Cite
|
Sign up to set email alerts
|

Caspase-8 controls the gut response to microbial challenges by Tnf-α-dependent and independent pathways

Abstract: ObjectivesIntestinal epithelial cells (IEC) express toll-like receptors (TLR) that facilitate microbial recognition. Stimulation of TLR ligands induces a transient increase in epithelial cell shedding, a mechanism that serves the antibacterial and antiviral host defence of the epithelium and promotes elimination of intracellular pathogens. Although activation of the extrinsic apoptosis pathway has been described during inflammatory shedding, its functional involvement is currently unclear.DesignWe investigated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
96
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(104 citation statements)
references
References 28 publications
6
96
1
1
Order By: Relevance
“…51,52 (ii) In addition to masking the potential role of the NAD + -sirtuin axis, recent observations indicate that these inhibitors can promote the production of soluble factors, including a number of cytokines (IL-6, IL-1β, IL-8, GM-CSF and CXCL2), chemokines (CCL2, RANTES and CXCL1) 53 and type I interferons (in response to mitochondrial damage) 54,55 that could interfere with the necroptotic signaling pathway. [56][57][58] Although the present study confirms previously reported observations suggesting a role for SIRT2 in promoting necroptosis, 33 they are at apparent odds with the observation that SIRT2-KO mice remain sensitive to the in vivo toxicity of exogenously administered TNF. 50 Possible explanations for this apparent discrepancy include the possible functional redundancy between sirtuin members as this multigene family often share substrate specificity 49 and the uncertainty concerning the mechanism underlying TNF toxicity in SIRT2-KO mice.…”
Section: Discussioncontrasting
confidence: 54%
“…51,52 (ii) In addition to masking the potential role of the NAD + -sirtuin axis, recent observations indicate that these inhibitors can promote the production of soluble factors, including a number of cytokines (IL-6, IL-1β, IL-8, GM-CSF and CXCL2), chemokines (CCL2, RANTES and CXCL1) 53 and type I interferons (in response to mitochondrial damage) 54,55 that could interfere with the necroptotic signaling pathway. [56][57][58] Although the present study confirms previously reported observations suggesting a role for SIRT2 in promoting necroptosis, 33 they are at apparent odds with the observation that SIRT2-KO mice remain sensitive to the in vivo toxicity of exogenously administered TNF. 50 Possible explanations for this apparent discrepancy include the possible functional redundancy between sirtuin members as this multigene family often share substrate specificity 49 and the uncertainty concerning the mechanism underlying TNF toxicity in SIRT2-KO mice.…”
Section: Discussioncontrasting
confidence: 54%
“…Immunohistochemical analysis was performed on formalin-fixed and deparaffinized tissue sections from the distal mouse colon using the tyramide signal amplification (TSA) Cy3 System (PerkinElmer), as recommended by the manufacturer and as described previously (56). In brief, for antigen retrieval, sections were treated for 20 minutes with heated citrate buffer (10 mM, pH 6).…”
Section: Intracellular Cytokine Staining Isolated Clp Cells and In Vmentioning
confidence: 99%
“…Levels of inducible nitric oxide synthase, cyclooxygenase-2, serum CXCL1/KC (derived from keratinocytes) and amyloid A were also reduced in poly(IC)-treated mice [69]. However, other studies actually implicate TLR3 signalling in inducing acute injury in gut epithelia [70][71][72]. Intraperitoneal injection of rotavirus dsRNA resulted in severe injury in the small intestine as characterized by thinning of the intestinal wall, erosion of villi and the mucus membrane, and weight loss; Tlr3 -/-mice were protected from such effects [70][71][72].…”
Section: Intestinal Tractmentioning
confidence: 99%
“…However, other studies actually implicate TLR3 signalling in inducing acute injury in gut epithelia [70][71][72]. Intraperitoneal injection of rotavirus dsRNA resulted in severe injury in the small intestine as characterized by thinning of the intestinal wall, erosion of villi and the mucus membrane, and weight loss; Tlr3 -/-mice were protected from such effects [70][71][72]. Poly(IC) administration also upregulated serum levels of several cytokines including IL-15 and IFN- [70].…”
Section: Intestinal Tractmentioning
confidence: 99%
See 1 more Smart Citation